Avifauna Potential for the Development of Bird Watching Ecotourism on Mount Tandikek - Rudi Yuliandri; Ramadhan Sumarmin (UNIVERSITAS NEGERI PADANG, 2020)
One of the economic benefits of birds is the development of birdwatching ecotourism. Birdwatching ecotourism can make recreation more effective and beneficial. Mount Tandikek with a high level of biodiversity is one area that has the potential to become a birdwathing ecotourism location. Based on this background, this research is important to do. this was done in June 2019 until July 2019 using the Point Count method combined with the Visual Encounter Survey (VES) method. Observation starts in the morning until late afternoon by following the hiking trail via Singgalang Gantiang from the bottom up. The data obtained were processed descriptively, and the diversity index and evenness index were calculated. The results obtained as many as 136 individuals from 35 species of birds during observation. There are 5 species of birds protected by PP. No. 7 of 1999, among them: Spilornis cheela, Spizaetus alboniger, Falco peregrinus, Todiramphus chloris and Nectarinia jugularis. The bird diversity index on Mount Tandikek is high with H '= 3.084. The average category of the binary evenness index is 0.628. The species of birds that dominated the observation were Phylloscopus trivirgatus for 16 individuals, Ficedula westermanni for 15 individuals and Pericrocotus miniatus for 14 individuals. Bird species found on Mount Tandikek have the potential to become birdwatching ecotourism objects.